2019
DOI: 10.1186/s12885-019-6000-y
|View full text |Cite
|
Sign up to set email alerts
|

Salvage PRRT with 177Lu-DOTA-octreotate in extensively pretreated patients with metastatic neuroendocrine tumor (NET): dosimetry, toxicity, efficacy, and survival

Abstract: Background NETTER-1 trial demonstrated high efficacy and low toxicity of four cycles of Peptide Receptor Radionuclide Therapy (PRRT) in patients with metastasized NET. The present study evaluates the outcome of further PRRT cycles in the so called salvage setting in patients after initial response to four therapy cycles and later progression. Methods Thirty five patients (pat.) (25 male, 10 female, 63 ± 9 years) with progressive, metastasized NET (23 small intestinal, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 27 publications
8
71
0
1
Order By: Relevance
“…It has also been demonstrated that absorbed doses delivered to healthy organs and tumours have large interpatient variability [5][6][7][8]. Moreover, many studies have provided evidence of dose-effect correlations in PRRT [9][10][11]. For these reasons groups from different hospitals and research institutes across Europe have proposed the use of dosimetry for PRRT in routine clinical practice [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that absorbed doses delivered to healthy organs and tumours have large interpatient variability [5][6][7][8]. Moreover, many studies have provided evidence of dose-effect correlations in PRRT [9][10][11]. For these reasons groups from different hospitals and research institutes across Europe have proposed the use of dosimetry for PRRT in routine clinical practice [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been demonstrated that absorbed doses delivered to healthy organs and tumours have large inter-patient variability [5][6][7][8]. Moreover, many studies have provided evidence of dose-effect correlations in PRRT [9][10][11]. For these reasons, groups from different hospitals and research institutes across Europe have proposed the use of dosimetry for PRRT in routine clinical practice [12].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast a previous smaller study including 35 mainly GI and BP G2 NET showed the shortest PFS of six months. This is surprising as progression in that study was de ned according to RECIST (response evaluation criteria in solid tumors) which would statistically lead to a longer PFS compared to the studies using clinical progression [37].…”
Section: Discussionmentioning
confidence: 92%